Investigating the deindustrialisation process in Zimbabwe since 1980 - Zivanai, Brenda (Midlands State University, 2017)
The study investigated deindustrialisation in Zimbabwe from 1980 which has become a major concern for the economy. The study mainly focused on the manufacturing sector in Zimbabwe. The researcher establishes through other researchers that deindustrialization in developed countries come as a result of economic development whilst developing countries is a result of an economy which is failing. The study identified the causes of deindustrialization in Zimbabwe such as sanctions, lack of funding, lack of foreign direct investment, poor technology and machinery. Also the effects of deindustrialisation were identified as high unemployment, low capacity utilization, brain drain, rise of informal sector, low contribution to Gross Domestic Product. The strategies which the government is implementing were also identified such as import substitution, disbursing of loans to industries, improvement of infrastructure, adjustments on the indigenization policy. The study also noted the improvements the industry has made so far and recommendations on what should be done for the resuscitation of the manufacturing sector was given.